2016
DOI: 10.3390/molecules21081065
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activities of the Essential Oil from Erigeron floribundus

Abstract: Erigeron floribundus (Asteraceae) is an herbaceous plant widely used in Cameroonian traditional medicine to treat various diseases of microbial and non-microbial origin. In the present study, we evaluated the in vitro biological activities displayed by the essential oil obtained from the aerial parts of E. floribundus, namely the antioxidant, antimicrobial and antiproliferative activities. Moreover, we investigated the inhibitory effects of E. floribundus essential oil on nicotinate mononucleotide adenylyltran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…The toxicity of monoterpene hydrocarbons against T. brucei can be attributed to the high hydrophobicity of this class of compounds, which are able to easily cross the cell membrane, causing the destabilization of phospholipid bilayers and the alteration of their permeability, leading to cell damage and death [ 44 , 55 ]. Among these compounds, the most abundant was sabinene (43.9%) ( Figure 1 ) which showed an IC 50 value against T. brucei of 5.96 µg/mL, which is close to that of the African cardamom essential oil (7.65 µg/mL) ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The toxicity of monoterpene hydrocarbons against T. brucei can be attributed to the high hydrophobicity of this class of compounds, which are able to easily cross the cell membrane, causing the destabilization of phospholipid bilayers and the alteration of their permeability, leading to cell damage and death [ 44 , 55 ]. Among these compounds, the most abundant was sabinene (43.9%) ( Figure 1 ) which showed an IC 50 value against T. brucei of 5.96 µg/mL, which is close to that of the African cardamom essential oil (7.65 µg/mL) ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The cell culture conditions and the growth inhibition assay on T. brucei and Balb/3T3 cells were performed as described before [ 44 ]. T. brucei TC221 bloodstream forms and mouse embryonic fibroblast Balb/3T3 cells (ATCC no CCL-163) were cultivated in vented plastic flasks at 37 °C with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have demonstrated the properties of sesquiterpenes; their oxygenated forms have a wide spectrum of biological activities, participating as inducers of plant defense mechanisms as well as important antimicrobial properties. This activity has been related with the presence of one or both an unsaturated double bond or oxygen-containing functional group (Kramer and Abraham 2012;Petrelli et al 2016;Wu et al 2005). In plant-microbe associations, sesquiterpenes are crucial for the establishment of the interaction, an example is when Laccaria bicolor interacts with Populus or Arabidopsis plants (Ditengou et al 2015), highlighting the relevance of secondary metabolites in biological interactions.…”
Section: Discussionmentioning
confidence: 99%
“…However, some essential oils extracted from other plants exert weaker antimicrobial activity against the bacteria tested herein because of weaker inhibition of bacterial growth, higher MIC values, or a demonstrated bacterial resistance [ 60 68 ]. These results, when compared with those obtained in the present study, reveal the more promising antibacterial power of M. urundeuva essential oil, likely because it contains specific active components.…”
Section: Discussionmentioning
confidence: 99%